A Comprehensive Review Of ICT Integration In Enhancing Physics Education - Ansarullah Hasas; Wahidullah Enayat; Musawer Hakimi; Ezatullah Ahmady (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
This comprehensive review explores the landscape of Information and Communication Technology (ICT) integration strategies in physics education, aiming to provide a holistic understanding of the current state of affairs and offer insights for future developments. The review synthesizes findings from a diverse range of studies, encompassing various ICT tools and methodologies employed in physics education globally. The analysis begins by identifying key ICT integration strategies that have demonstrated efficacy in enhancing student engagement and learning outcomes. The review sheds light on the evolving role of technologies such as Learning Management Systems (LMS), multimedia tools, and flipped classroom models in the physics education domain. Notably, the synthesis underscores the importance of considering cultural contexts and the need for cross-cultural comparisons in studying ICT integration. Challenges and opportunities associated with ICT integration are critically examined, emphasizing issues of access, instructor preparedness, and potential biases in existing literature. The implications of these challenges extend to recommendations for future research, including the necessity for longitudinal studies, cross-cultural investigations, and exploration of under-researched areas. Moreover, the review highlights the impact of ICT integration on diverse student populations and advocates for a more inclusive approach in designing educational interventions. The research implications encompass the identification of effective strategies, exploration of understudied areas, and the need for professional development interventions to enhance instructor readiness. This abstract encapsulates a roadmap for future research, emphasizing the potential of longitudinal studies, cross-cultural comparisons, and investigations into the impact of ICT integration on diverse student cohorts. Overall, this review contributes to the ongoing discourse on optimizing physics education through the judicious integration of Information and Communication Technologies.